Attitudes About Internet Support Groups Among Adolescents and Young Adults with Neurofibromatosis Type 1 and their Parents. Issue 5 (28th January 2014) - Martin, Staci; Wolters, Pamela L.; Baldwin, Andrea; Roderick, Marie Claire; Toledo‐Tamula, Mary Anne; Gillespie, Andrea; Widemann, Brigitte
Abstract: Youth with neurofibromatosis type 1 (NF1) have multiple, complex symptoms associated with physical, social‐emotional, and cognitive difficulties. In addition, caring for a child with NF1 can be extremely challenging for parents. Since research with other chronic illness populations suggests that social support, including internet support groups (ISGs), can be beneficial, this survey study aimed to determine the attitudes and preferences of adolescents and young adults with NF1 and parents of a child with NF1 regarding ISGs. Thirty patients and 30 caregivers completed a 24‐item survey about ISGs. Many patients and parents are not aware of any ISGs for NF1, but are interested in using one in the future for a variety of reasons, including to get answers to their questions about NF1, to find out about research studies, and to discuss problems and concerns about NF1. Specific concerns of interest include physical, social‐emotional, and cognitive aspects of NF1. ISGs have potential as a social support intervention within the NF1 community. ISGs for the NF1 population should include patients with NF1 (or parents of children with NF1) as well as a health professional, and both chat rooms and discussion boards likely would be well‐received.